?pARAMETRIC STUDY OF INCLINED PLANE SIEVING - YousufZai, M.Ayub Khan (Biological Sciences - PJSIR, 1996)
This paper presents the study of different parameters affecting the sieve fractionation of powders over an inclined plane. In this investigation coal powder hasbeenused to seehow theshapeof the fineparticles modifiesthe behaviour of the powder moving down the inclinedplane. It hasbeen indicated that the mean size of the fractions of the powder passing through the sieve atdifferent anglesof inclination (8) isessentially constant andis independent of the amount of the powder passed. The amount of powder passed through the sieves drops off drastically. In such a setup sieving could be very quickly achieved in relatively shortdistances.This investigation wouldbe veryimportant in developing automatic sieving procedures.